Cochrane Database of Systematic Reviews 2002
DOI: 10.1002/14651858.cd002811
|View full text |Cite
|
Sign up to set email alerts
|

Coasting (withholding gonadotrophins) for preventing ovarian hyperstimulation syndrome

Abstract: 4 95%CI includes no effect and appreciable benefit or harm 5 95%CI includes both no effect and appreciable benefit and apreciable harm xxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxxx 5 Coasting (withholding gonadotrophins) for preventing ovarian hyperstimulation syndrome (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 22 publications
0
21
0
2
Order By: Relevance
“…Reported E 2 cut-offs for initiation of coasting have varied from 2,500 pg/mL (9,175 pmol/L) (20) to 6,000 pg/mL (22,020 pmol/L) (21). Although randomized trials are lacking (22), large retrospective series suggest a lower incidence of OHSS in coasted cycles than would be expected from the literature (23,24).…”
mentioning
confidence: 99%
“…Reported E 2 cut-offs for initiation of coasting have varied from 2,500 pg/mL (9,175 pmol/L) (20) to 6,000 pg/mL (22,020 pmol/L) (21). Although randomized trials are lacking (22), large retrospective series suggest a lower incidence of OHSS in coasted cycles than would be expected from the literature (23,24).…”
mentioning
confidence: 99%
“…Although coasting is one of the most common strategies for preventing OHSS and is considered to be of great benefit because a significant decrease in estradiol levels is clear, there are a lack of randomized controlled trials (RCT) in which coasting is compared to not coasting. The evidence is still insufficient to determine whether coasting is an effective strategy for preventing OHSS [28], and the incidence OHSS can be as high as 9.4% even with coasting [29].…”
Section: Coastingmentioning
confidence: 99%
“…Only one study of which we are aware calculated a cumulative pregnancy rate for patients undergoing either of these strategies. Tummon et al (11) found a cumulative pregnancy rate of 77% in a series of 30 patients who were undergoing cryopreservation of all embryos. To our knowledge, this parameter has not been previously assessed in coasting cycles.…”
mentioning
confidence: 99%
“…A qualitative systemic review concluded that coasting results in acceptable pregnancy rates but does not completely avoid the risk of OHSS (10). A Cochrane review found insufficient prospective evidence to indicate whether coasting affects either the incidence of OHSS or pregnancy rates (11). Similarly, cryopreservation of all embryos has been the subject of several retrospective series, which have indicated a reduction in OHSS risk and acceptable pregnancy rates (12)(13)(14).…”
mentioning
confidence: 99%